Human Neural Stem Cell Induced Functional Network Stabilization After Cortical Stroke: A Longitudinal Resting-State fMRI Study in Mice - Minassian, Anuka; Green, Claudia; Diedenhofen, Michael; Vogel, Stefanie; Hess, Simon; Stoeber, Maren; Radmilovic, Marina Dobrivojevic; Wiedermann, Dirk; Kloppenburg, Peter; Hoehn, Mathias (Frontiers in Cellular Neuroscience, 2020)
Most stroke studies dealing with functional deficits and assessing stem cell therapy produce extensive hemispheric damage and can be seen as a model for severe clinical strokes. However, mild strokes have a better prospect for functional recovery. Recently, anatomic and behavioral changes have been reported for distal occlusion of the middle cerebral artery, generating a well circumscribed cortical lesion, which can thus be proposed as mild to moderate cortical stroke. Using this cortical stroke model of moderate severity in the nude mouse, we have studied the functional networks with resting state functional magnetic resonance imaging for 12 weeks following stroke induction Further, human neural stem cells were implanted adjacent to the ischemic lesion, and the stable graft vitality was monitored with bioluminescence imaging. Differentiation of the grafted neural stem cells was analyzed by immunohistochemistry and by patch clamp electrophysiology. Following stroke induction, we found a pronounced and continuously rising hypersynchronicity of the sensorimotor networks including both hemispheres, in contrast to the severe stroke filament model where profound reduction of the functional connectivity had been reported by us earlier. Vitality of grafted neural stem cells remained stable throughout the whole 12 weeks observation period. In the stem cell treated animals functional connectivity did not show hypersynchronicity but was globally slightly reduced below baseline at 2 weeks post stroke, normalizing thereafter completely. Our resting state fMRI studies on cortical stroke reveil for the first time a hypersynchronicity of the functional brain networks. This hypersynchronicity appears as a hallmark of mild cortical strokes, in contrast to severe strokes with striatal involvement where exclusively hyposynchronicity have been reported. Effect of the stem cell graft was an early and persistent normalization of the functional sensorimotor networks across the whole brain. These novel functional results may help interpret future outcome investigations after stroke and demonstrate the highly promising potential of stem cell treatment for functional outcome improvement after stroke.